Biophysical Environmental Characteristics The Marunggai River Restricted Area, Padang Pariaman Districts, West Sumatera Province. - Nur Azizah; M. Fauzi M. Fauzi; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstracIn the Marunggai River there is a restricted area and it is known as “lubuk larangan”, as it is a habitat of Tor tambroides, a rare endemic fish species. A research aims to find out a proper method to manage the Marunggai River restricted area in order to safe the T. tambroides population was conducted in ApriltoAugust 2019. The water was sampled 3 times in the buffer and conservation zones.Water quality parameters in the habitat of T.tambroideswere as follows: temperature23,6 - 25,1 °C, transparency37-110 cm, depth37-110 cm pH 6, DO4,86 - 5,46 mg/L free CO22,75-3,15 mg/Land phytoplankton abundance was201-1.003 sel/L.Keyword: Tor sp,endemic fish, buffer zone, conservation area, Water quality